Distance learning as a direction of reforming public administration in the field of higher education - Білоус-Осінь, Тетяна Ігорівна; Білоус-Осінь, Т. І.; Билоус-Осень, Татьяна Игоревна; Bilous-Osin, Tetiana I.; Козачук, Діана Анатоліївна; Козачук, Д. А.; Козачук, Диана Анатольевна; Kozachuk, Diana A. (Riga : Izdevniecība “Baltija Publishing”, 2020)
The article is devoted to the study of theoretical and legal bases of changing the vector of public administration in the field of higher education to distance learning. The process of distance learning is defined as the transfer of information of a certain content (knowledge, skills, abilities), the ultimate goal of which is the ability of the higher education recipients 47to use this information in their activities. The main characteristics of the process of information transfer within distance learning include: 1) the main cognitive process through which the process of transmission, assimilation and application of information by the higher education recipient; 2) the level and nature of feedback from the higher education recipient in the learning process, as well as the degree of adaptation of the learning process to the individual characteristics of the higher education recipient: psychological structure of personality, sociological structure of personality, level of learning and ability to learn; management style of the learning process, which is basedon the principled recognition or non-recognition of the fact of individuality of the student’s personality and can be authoritarian or humanistic. It is proposed to establish a national Council of Ukraine for Distance Education under the Ministry of Education and Science of Ukraine, the main task of which will be institutional and legal support for the introduction of various forms of distance learning in higher education, taking into account globalization and humanization; elaboration of a simplified procedure for licensing distance forms of education in higher educational institutions; development of a single concept of creating a network of open universities in Ukraine, which carry out educational activities in various specializations, etc.

Стаття присвячена дослідженню теоретико-правових засад зміни вектора державного управління у сфері вищої освіти на дистанційне навчання. Процес дистанційного навчання визначається як передача інформації певного змісту (знань, умінь, навичок), кінцевою метою якої є здатність здобувачів вищої освіти використовувати цю інформацію у своїй діяльності. До основних характеристик процесу передачі інформації в рамках дистанційного навчання можна віднести: 1) основний пізнавальний процес, за допомогою якого здійснюється процес передачі, засвоєння та застосування інформації здобувачем вищої освіти; 2) рівень і характер зворотного зв'язку здобувача вищої освіти в процесі навчання, а також ступінь адаптації процесу навчання до індивідуальних особливостей здобувача вищої освіти: психологічна структура особистості, соціологічна структура особистості, рівень навчання та вміння вчитися; стиль управління процесом навчання, який ґрунтується на принциповому визнанні чи невизнанні факту індивідуальності особистості учня і може бути авторитарним або гуманістичним. При Міністерстві освіти і науки України пропонується створити національну раду України з дистанційної освіти, основним завданням якої буде інституційно-правове забезпечення впровадження різних форм дистанційного навчання у вищих навчальних закладах з урахуванням глобалізації та гуманізації; розроблення спрощеного порядку ліцензування дистанційних форм навчання у вищих навчальних закладах; розробка єдиної концепції створення в Україні мережі відкритих університетів, які здійснюють освітню діяльність за різними спеціалізаціями тощо.
Bilous-Osin T. I. Distance learning as a direction of reforming public administration in the field of higher education / T. I. Bilous-Osin, D. A. Kozachuk // Public administration under modern conditions: concept, features, challenges : Collective monograph. - Riga : Izdevniecība “Baltija Publishing”, 2020. - P. 34-49.
Keywords: higher education; distance learning; Council of Ukraine for Distance Education; open universities; вища освіта; дистанційне навчання; Рада України з дистанційної освіти; відкриті університети; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education